2019
DOI: 10.48550/arxiv.1902.03333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

More concordance homomorphisms from knot Floer homology

Irving Dai,
Jennifer Hom,
Matthew Stoffregen
et al.

Abstract: We define an infinite family of linearly independent, integer-valued smooth concordance homomorphisms. Our homomorphisms are explicitly computable and rely on local equivalence classes of knot Floer complexes over the ring F[U, V ]/(U V = 0). We compare our invariants to other concordance homomorphisms coming from knot Floer homology, and discuss applications to topologically slice knots, concordance genus, and concordance unknotting number.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…Note that the notion of reducedness is preserved under basis changes of the form x i → x i + j∈J U j V m j x i j . We will use the grading conventions of [Zem19b]; see also [DHST19,Section 2]. Recall that multiplication by U lowers the Alexander grading by 1, multiplication by V raises the Alexander grading by 1, and the differential preserves the Alexander grading.…”
Section: The Fusion Number Of Cablesmentioning
confidence: 99%
“…Note that the notion of reducedness is preserved under basis changes of the form x i → x i + j∈J U j V m j x i j . We will use the grading conventions of [Zem19b]; see also [DHST19,Section 2]. Recall that multiplication by U lowers the Alexander grading by 1, multiplication by V raises the Alexander grading by 1, and the differential preserves the Alexander grading.…”
Section: The Fusion Number Of Cablesmentioning
confidence: 99%
“…If K is rationally slice, then both ±1 surgeries on K bound rational homology balls. Hence the τ -invariant [HW16], and ϕ jinvariants [DHST19] all vanish for K and its mirror. (On the other hand, it is not known if…”
Section: Introductionmentioning
confidence: 99%
“…We refer to the pair (CFK F[U ,V] (K), ι K ) as the ι K -complex of a knot K. Moreover, Zemke [Zem19b] (see also [Zem19a, Theorem 1.5]) showed that up to an algebraic equivalence called local equivalence, the ι K -complex of a knot is a concordance invariant. We use a slightly coarser equivalence relation called almost local equivalence, which is motivated by [DHST18] (see also [DHST19]), to show the following. Note that the following theorem implies Theorem 1.1 immediately since the (p, −1)-cable of a rationally slice knot is rationally slice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intuitively speaking, general satellite operations are quite different from the connected sum and hence often disregard the group structure of C. This feature has been exploited widely to construct linearly independent knots in various context (e.g. [4,5,7,12,20]). It is hence reasonable to expect Theorem 1.2 to be true, and it is even tempted to believe general iterated satellite knots are independent.…”
Section: Introductionmentioning
confidence: 99%